Transcapho perilunate dislocation with palmar extrusion of the scaphoid proximal pole - Marcuzzi, Augusto; Leigheb, Massimiliano (Acta Biomedica Atenei Parmensis, 2016)
Perilunate fracture-dislocations usually combine ligament ruptures, bone avulsions, and fractures in different patterns. Rarely a displaced fracture of the scaphoid can coexist with a scapho-lunate dissociation and can result in enucleation of the proximal pole. We report about a case of trans-scaphoid perilunate dislocation with palmar extrusion/enucleation of the scaphoid proximal pole, treated with scaphoid fracture open reduction and internal fixation with screw, scapho-lunate ligament repair with an anchor and vascularization of the scaphoid proximal pole with the 2nd intermetacarpal artery. At 52 months follow up we had good clinical and radiographic results. In conclusion, scientific literature including our experience about this rare complex lesion of the wrist is too weak to support an effective strategy of management but we think that the careful analysis of the single problems can be the key to solve the complexity. Goal of the treatment should be complete revascularization and healing of the scaphoid, avoiding non union and avascular necrosis; simultaneously a proper ligament reconstruction is fundamental to re-establish carpal stability. Prevention of carpal collapse for a SNAC o SLAC situation is essential to reach a good level of Quality of Life and satisfaction of the patient.